Study on the In Vitro Activity of Five Disinfectants against Nosocomial Bacteria - Montagna, Maria Teresa (Int J Environ Res Public Health, 2019)
Nosocomial infections cause significant morbidity and mortality worldwide, and the pathogenic organisms responsible for such infections can develop resistance to antimicrobial agents. Understanding the activity of disinfectants against clinical and environmental bacterial isolates is therefore crucial. We analysed the in vitro activity of five antimicrobial products (phenolic compounds, didecyldimethylammonium chloride (DDAC), sodium hypochlorite, isopropanol + ammonium compounds (IACs), hydrogen peroxide) against 187 bacterial strains comprising clinical isolates, as well as 30 environmental isolates of Pseudomonas aeruginosa from hospital water samples. Disk diffusion assays were employed to assess antimicrobial activity. Hydrogen peroxide was significantly more active (p < 0.0001) than the other disinfectants against all P. aeruginosa, Klebsiella pneumoniae, Enterococcus faecalis and Staphylococcus aureus strains. It was also the only disinfectant with activity against both clinical and environmental strains of P. aeruginosa. DDAC and IAC-based disinfectants were ineffective against Gram-negative strains, but showed significant activity (particularly IACs, p < 0.0001) against the Gram-positive strains. Compared with IACs, DDAC was significantly more active on E. faecalis and less active on S. aureus (p < 0.0001). Sodium hypochlorite and phenol compounds, by contrast, were inactive against all bacterial strains. The development of disinfection procedures that are effective against all microorganisms is essential for limiting the spread of nosocomial infections.